Assessing the genetic diversity of South African sweetpotato germplasm using DNA and protein markers - Selaocoe, Maleshoane Ellen (Vaal University of Technology, 2013)
Sweetpotato is one of the most important food crops in developing countries including South Africa. Currently two major types of cultivars are grown in South Africa: one is the orange-fleshed sweetpotato (OFSP) which has high β-carotene content, a precursor of vitamin A. The second type is the cream-fleshed sweetpotato (CFSP) which has low β-carotene content but is high in dry matter. Most South Africans prefer the CFSP although the OFSP offers more advantages. This presents a challenge to plant breeders to develop new varieties that will combine the desirable qualities of both the cultivars. To achieve this goal, plant breeders need knowledge about the genetic variation of the crop to develop an efficient breeding programme. This study assessed the genetic relationships of 28 orange- and cream-fleshed sweetpotato accessions by (i) examining the variation in leaf proteins, (ii) using random amplified polymorphic DNA (RAPD) and, (iii) using variation of the ITS region. The analysis of proteins, RAPD and variation of the ITS region polymorphism levels were 55.6%, 98% and 16.5%, respectively. Dendrograms generated from all the analyses generally clustered the accession according to their flesh colour and country of origin. Analysis of molecular variance (AMOVA) found a significant difference between OFSP and CFSP and a significant difference between the South African and non-South African germplasm. The high genetic diversity in the South African sweetpotato germplasm is a positive indicator for a breeding programme that has a number of targets such as breeding for nutritional improvement, disease resistance and drought tolerance
M. Tech. (Biotechnology, Department of Biosciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Sweetpotato; Food crops; Dissertations, Academic -- South Africa.; Sweet potatoes.